The eﬀect of additive dosages on crepe quality produced - Sherly Hanifarianty; Afrizal Vachlepi; Mili Purbaya (Majalah Kulit, Karet, dan Plastik, 2021)
Thin Pale Crepe (TPC) products are currently increasing in demand by rubber product manufacturers. Its production process is relatively more efcient than crumb rubber, which is Indonesia’s main product. The drying of TPC products still uses air drying from the burning of rubberwood. The use of rubberwood is predicted to be less economical in the future. With an increasing limited natural forest, rubberwood will be an alternative substitute for wood from natural forests. As a result, the economic value of rubberwood will be even greater which will have an impact on the increasing cost of TPC products if it continues to use rubberwood as fuel. Therefore, we need an alternative to rubberwood as an energy source for drying TPC. Sunlight can be an alternative source of energy that can be maximized for the drying process of natural rubber, including in TPC production. This research was conducted in two stages, namely 1) the production of TPC using latex from various clones with several additive dosages, and 2) TPC drying using various renewable energy sources. The results of research activities are in the form of a technology package regarding the TPC production process using renewable energy sources. The results showed that the TPC products produced with various treatments fulflled SNI 1903-2000. The three clones (BPM 24, PB 260, and GT 1) were able to produce TPC with bright yellow color.